Bis(triarylmethylium)‐type Macrocyclic Dications: Mechanochromic Emission Extending to the Red Region. Issue 3 (23rd March 2023) - Ishigaki, Yusuke; Tachibana, Takuya; Sugawara, Kazuma; Kikuchi, Moto; Suzuki, Takanori
Abstract: Macrocyclic dications 2 2+ composed of two triarylmethylium units were designed and synthesized. In contrast to the reference monocations 1 +, macrocyclic dications 2 2+ exhibited mechanochromic emission extending to the red region (−900 nm), since the luminescence color in a solid state can reversibly change due to their constrained structures granted by alkylene linkers and the choice of a proper counterion. X‐ray diffraction and spectroscopic analyses revealed that such mechanochromic behavior was induced by the crystal‐to‐amorphous transition. A change in the intermolecular interaction of macrocyclic dications 2 2+ would be the key to realizing a change in the emission pattern, since the color of the molecules did not change by applying mechanical stimuli. These findings may suggest a design strategy for creating a variety of stimuli‐responsive materials, especially for carbocation‐based fluorescent materials. Abstract : Since triarylmethyliums absorb visible light, their emissions can be extended to longer wavelengths than their absorptions. The constrained structure of macrocyclic dications is the key to realizing the emission extending to the red region. Thus, tethered macrocyclic dications exhibit NIR‐mechanofluorochromism induced by the crystal‐to‐amorphous transition.